Marine and Coastal Legislation in Costa Rica: Overview, Limitations and Strengths - Cajiao, María Virginia (2005)
Environmental law is the group of norms that regulate  man´s  behavior  in  society  as  well  as the environment and the natural resources. The regulations concerning the coastal-marine norms are  under  International  Legislation  Agreements such  as  the  United  Nations  treaty  to  the  Sea Right,  the  Ramsar,  Cites,  and  the  Biological Diversity among others. Nationwide, the Political Constitution contains some laws and sets of rules that  directly  regulate  aspects  like  the  marine-terrestrial  zone,  the  fishing,  the  wildlife,  the turtles, and the cetaceans among others. However, these rules have some limitations and there also exists a lack of inter-institutional coordination. All this results in a poor ocean governability.